The syntax of discourse functions in Greek: a non-configurational approach - Alexopoulou, Theodora (The University of Edinburgh, 1999)
This thesis offers an account of the syntactic properties of Focus-movement, Topicalisation and Clitic Left Dislocation (CLLD) in Greek. As these phenomena are central to discussions of the syntax-discourse interface, a significant part of this study pursues the question of the representation of the discourse functions of topic and focus and their relation to syntax.

For the most part, the literature on the syntax of Focus-movement, Topicalisation and CLLD advocates that focus and topic are encoded in the Phrase Structure by distinct Func¬ tional Projections: Focus Phrase (FP) and Topic Phrase (TP). Foci and topics move to the Specifier of the relevant Projection to check their discourse features. The term Discourse Configurational Languages has been recently coined for languages that encode focus and topic through Phrase Structure configurations.

With respect to the syntactic properties of the relevant structures, the Discourse Configurational approach assumes that Focus-movement, Topicalisation and CLLD instantiate three distinct syntactic operations; A-bar-movement, A-movement and base-generation respectively. This complex syntax enables a simple view of the syntax-discourse interface; there is an isomorphic relation between syntax and discourse, as each discourse function is associated with a distinct syntactic operation. Further, focus and topic are treated as syntactic features, specifying heads of Functional Projections.

This thesis, in contrast, argues for a non-configurational approach. It shows that the claim that Focus-movement and Topicalisation instantiate A-bar-movement and A-movement respectively is based on insufficient evidence. This claim is motivated by the absence of weak crossover effects in Topicalisation and their presence in Focus-movement. However, this study argues that the weak crossover effect is not a valid diagnostic of the A/A-bar distinction, since some cases of Wh-questions, the prototypical instance of A-bar movement, do not give rise to weak crossover effect. Further, in the Discourse Configurational approach, CLLD is treated as an instance of base-generation rather than movement, because it does not license parasitic gaps. In this thesis, CLLD is analysed as adjunct extraction and it is shown that the unavailability of parasitic gaps is a general property of adjunct extraction. Further, this study demonstrates that Focus-movement, Topicalisation and CLLD exhibit the same syntactic properties and instantiate the same extraction mechanism. Thus, they are given a unified syntactic treatment.

The argument that Focus-movement, Topicalisation and CLLD share the same syntax has implications for the architecture of the discourse-syntax interface. Unlike the Discourse Configurational approach, this syntactic analysis implies a non-isomorphic relation between syntax and discourse, as a single syntactic structure corresponds to more than one discourse function. Thus, the syntax of discourse constructions is independent of the discourse func¬ tions encoded. It is argued that the discourse evidence does not justify the incorporation of discourse functions in Phrase Structure or their treatment as syntactic features. Rather, focus and topic should be represented at a distinct level, independent of syntax, Information Structure.

The analysis is couched in the framework of Head-driven Phrase Structure Grammar. The syntactic properties of extractions in Greek are readily captured by the HPSG mechanism of Unbounded Dependencies. The multidimensional nature of HPSG signs allows for the representation of discourse functions and a flexible mapping between syntax and discourse.